Legal Protection of Children as Persons of Criminal Abuse in the Investigation Process at Polres Aceh Tenggara - Indra Gunawan Purba; Ervina Sari Sipahutar; Erikson Napitupulu (SIASAT, 2023)
Children as perpetrators of crimes will also experience a legal process that is identical to adults who commit crimes, the meaning of the word identical here means "almost the same", which differs only in the length and way of handling it. Facing and handling the juvenile justice process involved in a crime, the first thing that should not be forgotten is to look at his position as a child with all of his special characteristics and characteristics, thus the orientation is based on the concept of protection of children in the process of handling them so that things this will be based on the concept of child welfare and the interests of the child. Handling children in the legal process requires an approach, service, treatment. The Southeast Aceh Resort Police as the leading institution in law enforcement has a sizable responsibility to harmonize the duties and authorities of the Police, especially in Southeast Aceh District as stipulated in Law Number 2 of 2002 concerning the Indonesian National Police, in dealing with children in conflict By law, the police always have to pay attention to the condition of children who are different from adults. The nature of children as individuals who are still unstable, the future of children as national assets, and the position of children in society who still need protection can be used as a basis for finding an alternative solution how to prevent children from a formal criminal justice system, placing children in prison, and stigmatization of position of the child as a convict. The investigation process is an initial stage where a child is confronted with the police. Irregularities that usually often occur in the process of investigating child crimes in the form of abuse, beatings and other bad treatment certainly experience obstacles so that efforts are needed to achieve the goal of protecting children who are in conflict with the law, especially perpetrator of the crime of torture.